Combined sustained release of BMP2 and MMP10 accelerates bone formation and mineralization of calvaria critical size defect in mice - Ricardo Reyes; Jose Antonio Rodríguez; Josune Orbe; María Rosa Arnau; Carmen Évora; Araceli Delgado (Taylor & Francis Group, 2018)
The effect of dual delivery of bone morphogenetic protein-2 (BMP-2) and matrix metalloproteinase 10 (MMP10) on bone regeneration was investigated in a murine model of calvarial critical-size defect, hypothesizing that it would result in an enhanced bone formation. Critical-size calvarial defects (4 mm diameter) were created in mice and PLGA microspheres preloaded with either BMP-2, MMP10 or a microsphere combination of both were transplanted into defect sites at different doses. Empty microspheres were used as the negative control. Encapsulation efficiency was assessed and in vivo release kinetics of BMP-2 and MMP10 were examined over 14 days. Histological analyses were used to analyze bone formation after four and eight weeks. Combination with MMP10 (30 ng) significantly enhanced BMP-2 (600 ng)-mediated osteogenesis, as confirmed by the increase in percentage of bone fill (p < .05) at four weeks. Moreover, it also increased mineral apposition rate (p < .05), measured by double labeling with tetracycline and calceine. MMP10 accelerates bone repair by enhancing BMP-2-promoted bone healing and improving the mineralization rate. In conclusion combination of MMP10 and BMP-2 may become a promising strategy for repair and regeneration of bone defects.